The challenges using Bitcoin as a payment intermediationc: a study in Iceland - Svavar Hjaltested 1980- (2022)
Payment intermediation is constantly evolving and innovating due to financial technology's possibilities. The introduction of financial technology has created a new environment for financial markets, which has called for the need to implement new directives in the law on payment intermediation. These directives, PSD and PSD2, offer new opportunities and change the landscape of payment intermediation for service providers, consumers, and competition in the market. Payment intermediation is constantly evolving due to the possibilities offered by its introduction of financial technology. With the advent of new companies, technology, and competition from new entrants to the market, finances will change. Many financial technology companies have been established in recent years and compete to find new solutions that save us time in our daily activities and simplify our lives, and the financial technology environment in Iceland is by no means excluded from this development. Consumers' demands change in line with current technological developments. We will take a look at the concept of payment intermediation. The development is driven by companies that use blockchain technology and other transformation technologies to respond to changing consumer behaviors and provide more accessible and faster services from the digital generations. Financial technology is the future, and with a vital education, efficient processes, and clear advantages in the market, everyone benefits. The payment instrument that is considered most likely to receive cash is electronic money, which is based on blockchain technology and would be issued by central banks.